A Rare Form of Chronic Granulomatous Disease (Type Iva) Presenting as Inflammatory Bowel Disease - Francisco A Sylvester (Canadian Journal of Gastroenterology)
Neutrophil dysfunction syndromes can sometimes mimic the clinical and pathological features of inflammatory bowel disease. The case of a 3.5-year-old boy with chronic diarrhea, abdominal pain, poor growth since infancy and microcytic, hypochromic anemia is presented. After an extensive diagnostic evaluation, he was found to have a rare variant (type IVA) of chronic granulomatous disease. His gastrointestinal symptoms markedly improved during therapy with gamma-interferon. Chronic granulomatous disease can present initially with a clinical picture suggestive of chronic intestinal inflammation. Therefore it should be considered in the differential diagnosis of atypical inflammatory bowel disease, both in children and young adults.